The role of Nazi organizations in German repatriation from the Baltic states (1939-1941) - Jakubavičienė, Ingrida (Lietuvos istorijos studijos, 2006)
In 1939 the Baltic states became the victims of cruel Hitler and Stalin agreements. Hitler and Stalin agreed that the German minority from the Baltic states would repatriate to Germany. Since 1939 till 1944 more than one million Germans were forced to leave over 40 states and settle down in Germany. In 1923, in Lithuania, there lived 28 thousand 671 Germans or 1.5 percent of the population. In 1940, there were 36 thousand Germans. The number of Germans increased because of Nazi agitation, then Lithuanians changed their nationality into German. In Latvia in 1930, there lived about 70 thousand, and in Estonia—16 thousand Germans. In 1939, more than 50 thousand Germans repatriated from Latvia, and about 13 thousand 700 Germans from Estonia. In 1940, again 18 thousand Germans were forced to leave Estonia and Latvia. The repatriation from Lithuania was executed in the winter of 1941; more than 50 thousand Germans and Lithuanians left the country. German historians ascribed the preparation for repatriation to the German community. In fact, the German community was directed by local Nazi organizations and its leaders. German historians agree that the news from Berlin about the German repatriation was first given to the leaders of the Nazi movement in the Baltic states. Although there are some historical researches, nobody noticed the important role played by the Nazi organizations during the German repatriation. The leaders of the Nazi movement in the Baltic states were at the same time the leaders of the German community. The Nazi movement had thousands of members, it received instructions and financial support from Berlin. German historians made an impression that the German community obeyed Hitler’s order and did its best to leave the country as quickly as possible. The German Nazi movement (Bewegung) was especially active in Latvia, led by Erhard Kroeger. The Nazi organization in Estonia was directed by Oskar Lutz and Baron Wrangel, the president of the German community. On the 25th of September 1939, E. Kroeger visited Hitler in his staff in Poland. E. Kroeger informed Hitler about the political situation in Latvia and asked him to rescue the Baltic Germans. During the secret negotiations between Hitler and Stalin, the question of Germans in the Baltic states was discussed too. On the 2nd of October, the leaders of the Baltic Nazi organizations were informed about Hitler’s decision to transfer the German minority from Estonia and Latvia to Germany. On the 6th of October, Hitler officially proclaimed the repatriation from the Baltic states. The "Rigasche Rundschau" published the proclamation of E. Kroeger about the preparation for the repatriation. In three weeks, the Germans abdicated their previous citizenship, transferred their personal property to special German institutions, and with small luggage, left the country. In autumn of 1939, the Nazi organization Kulturverband in Lithuania also started preparation for German repatriation. But the negotiations with Lithuanian authorities did not start. After secret agreements between Hitler and Stalin, Lithuania should be handed to the Soviets. The German and Soviet negotiations started in 1940 after the Soviets occupied Lithuania. Although Hitler did not proclaim the German repatriation from Lithuania, practically the German minority was prepared for it. Berlin ordered Kulturverband to give real figures about the German minority in Lithuania. The leaders of Kulturverband, R. Kosmann, K. Cerpinski, O. Reichard, von der Ropp, and E. Klug controlled the community, spread the information about repatriation, and followed the instructions from Berlin. The leaders of Kulturverband were told about the place where the German minority from Lithuania would be settled down. In comparison with the repatriation from Latvia and Estonia, the Lithuanian German minority experienced hardship and suffered losses because the preparation continued for about two years (since October 1939 till March of 1941). Nazi organizations in the Baltic states fulfilled the instructions of the German SS and other institutions: made registration of Germans and their property, gave new documents for the repatriates, and spread the information. Nazi organizations in the Baltic states helped German institutions execute the repatriation in a short time.